Carrion's disease after blood transfusion. - Pons, Maria J (2015)
Bartonella bacilliformis is a pathogen that is endemic in some areas of the Andean region of Peru, southern Ecuador and southern Colombia. This pathogen causes so-called Carrion's disease, a biphasic disease with acute and chronic phases (called Oroya fever and "Peruvian wart" respectively1-3). In the absence or delay of antibiotic treatment, the mortality rate in the acute phase is up to 88%1. The acute phase is characterised by fever and severe anaemia and may be followed, several weeks or months later, by the chronic eruptive phase due to endothelial cell proliferation2. No animal reservoir has been identified to date and it is considered that healthy carriers act as a pathogen reservoir in endemic areas